2014
DOI: 10.1002/ptr.5129
|View full text |Cite
|
Sign up to set email alerts
|

Extracts of Devil's Club (Oplopanax horridus) Exert Therapeutic Efficacy in Experimental Models of Acute Myeloid Leukemia

Abstract: Acute myeloid leukemia (AML) is a group of hematological malignancies defined by expanded clonal populations of immature progenitors (blasts) of myeloid phenotype in blood and bone marrow. Given a typical poor prognostic outlook, there is great need for novel agents with anti-AML activity. Devil’s club (Oplopanax horridus) is one of the most significant medicinal plants used among the indigenous people of Southeast Alaska and the coastal Pacific Northwest, with different linguistic groups utilizing various par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…It was found that the compounds with higher anti-proliferative activity presented more potential cytotoxic effect on normal human hepatic cells as well (Table 1), which means these compounds may have potential hepatotoxicity in vivo. Actually, the safety and efficiency of O. horridus have not been evaluated totally thus far though it has a long history of use medicinally and as a dietary supplement [21,24], so more studies are definitely needed. …”
Section: Anti-proliferative Activity and Possible Structure-activity mentioning
confidence: 99%
“…It was found that the compounds with higher anti-proliferative activity presented more potential cytotoxic effect on normal human hepatic cells as well (Table 1), which means these compounds may have potential hepatotoxicity in vivo. Actually, the safety and efficiency of O. horridus have not been evaluated totally thus far though it has a long history of use medicinally and as a dietary supplement [21,24], so more studies are definitely needed. …”
Section: Anti-proliferative Activity and Possible Structure-activity mentioning
confidence: 99%
“…Next, the acetone extract was formulated into the drinking water of male C57BL/6J mice engrafted with C1498 cells. We have previously used this animal model of AML in experimental therapeutic studies (Barth et al, ; McGill et al, ; McGill, Brown, Cheng, et al, ). This included an evaluation of the anti‐AML efficacy of extracts from Devil's Club ( Oplopanax horridus ), which is another Alaskan medicinal plant with profound indigenous use (McGill et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Cellular viability assays were performed as previously described using a Cell Titer 96 AQueous Non‐Radioactive Cell Proliferation Assay according to the manufacturer's instructions (Promega, Madison, WI; Barth et al, ; Brown et al, ; McGill et al, ; McGill et al, ). Briefly, C1498 cells were incubated for 48 hr, whereas primary human AML samples were incubated for 96 hr, with control or experimental treatments, prior to cellular viability assays.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To generate the in vivo C1498 murine AML model, 1 x 10 6 C1498 cells were injected retro-orbitally into syngeneic eight-week-old female C57BL/6J mice (Jackson Labs, Bar Harbor, ME) [63]. LCL204 was dissolved in 30% v/v propylene glycol, 5% v/v Tween 80 and 65% of 5% w/v dextrose in water (PTD).…”
Section: Methodsmentioning
confidence: 99%